PENGARUH BAHAN ORGANIK DAN PUPUK KALIUM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN MELON (Cucumis melo L.) - Safuan, La Ode; Bahrun, Andi (Jurnal Agroteknos, 2012)
The aim of the research was study the effect of organic matter and potassium fertilizer on growth and production of melon. This research was conducted in Rahandouna Subdistrict, Poasia District, Southeast Sulawesi Province, from December 2009 until March 2010. This research was arranged on Split Plot Design, consisting of four levels of organic matter (B) as the main plot : without organic matter (B0), 5 ton.ha-1(B1), 10 ton.ha-1(B2), and 15 ton.ha -1(B3), and potassium fertilizer as the sub plot consisting of five levels: without potassium fertilizer (K0), 50 kg K2O.ha-1 (K1), 100 kg K2O.ha-1 (K2), 150 kg K2O.ha-1 (K3), and 200 kg K2O.ha-1 (K4). Research variables consisted of growth components (stem length, stem circumference, leaf number, and leaf area), production components (fruit weight, fruit circumference, fruit thickness). The result of the research showed that the interaction of organic matter and potassium fertilizer had no effect on all observed parameters. The aplication of organic matter 10-15 ton.ha-1 and potassium fertilizer 50-150 kg K20 increased growth and production of melon. The optimum dose of organic matter was 12,25 ton.ha-1 and potassium fertilizer at 150 kg K2O ha.-1 for fresh fruit production, and fruit weight production were 50,40 ton.ha-1 and 54,60 ton ha.-1, respectively. Keywords : fertilizer, growth, potassium, production, organic matter.